Factors contributing to variation in the use of multimodality treatment in patients with gastric cancer: A Dutch population based study. Issue 2 (February 2018) - Beck, N.; Busweiler, L.A.D.; Schouwenburg, M.G.; Fiocco, M.; Cats, A.; Voncken, F.E.M.; Wijnhoven, B.P.L.; van Berge Henegouwen, M.I.; Wouters, M.W.J.M.; van Sandick, J.W.; ,
Abstract: Background: Substantial variation in the use of (neo) adjuvant treatment in patients with gastric cancer exists. The aim of this study was to identify underlying (organizational and process) factors associated with the use of perioperative therapy. Patients and methods: Patients with resectable gastric cancer who underwent surgery between 2012 and 2014 were selected from the Dutch Upper gastrointestinal Cancer Audit (DUCA). The proportion of perioperatively treated patients was defined per hospital. Five hospitals with the lowest percentage (LP group) and 5 hospitals with the highest percentage (HP group) of perioperative therapy were identified. In the selected hospitals additional information was obtained from patients' medical records using a structured list with predefined variables. Results: In total, 429 patients (231 in LP group, 198 in HP group) from 9 different hospitals were included. Perioperative therapy was given in 16.0% of patients in the LP group compared to 40.4% in the HP group. In the LP group, patients were enrolled in a clinical trial less frequently (10.8% versus 26.8%, P <.001), and a higher percentage grade III-IV toxicity was observed during neoadjuvant treatment (25.7% versus 46.3%, P =.007). Multivariable analysis showed that, besides known casemix factors, consultation with ≥3 upper GI specialists prior to treatment decision was positively associated with initiating perioperative therapy (OR 2.08, 95% CI 1.19–3.66). Conclusion: Results of this study confirm considerable hospital variation in the use of perioperative therapy in patients with gastric cancer. Besides known casemix factors, use of perioperative therapy was associated with the level of involvement of multidisciplinary care.